As implicações da pandemia da COVID-19 nos serviços odontológicos, na vida e prática profissional dos cirurgiões-dentistas da rede pública municipal de Manaus - Amazonas - Naiff, Priscilla Farias (2023)
The COVID-19 pandemic led health authorities to establish policies and guidelines to be followed by the population, including the dental sector. This study aimed to analyze the implications of the pandemic in dental services, in the life and professional practice of dental surgeons in the municipal health network of Manaus. To subsidize an exploratory research with professionals through a questionnaire, a documentary review was carried out on the laws, ordinances, technical notes and memorandums that guided the work of dentists of the Municipal Health Secretaria of Manaus (SEMSA), in 2020 and 2021, made available by SEMSA. The application of a questionnaire through the Google Forms virtual platform was carried out and directed to dental surgeons. The questionnaire was sent to 177 professionals and 81 were included in the research. The collected data were stored in an Office Excel 2007 spreadsheet generated by Google forms. For categorical data, absolute and relative frequencies were obtained, and for qualitative analysis, content analysis was used with the aid of Atlas ti software, version 22. The results showed that, in general, the recommendations directed at the dental sector regarding adjustments to the work process in the dental environment were implemented at the municipal level, with few exceptions. Regarding the implications for the personal and professional lives of the interviewees, there was a withdrawal of dentists from their activities, including for long periods. The disease was also a source of constant stress and fear in these people's lives. Oral health workers had ample participation in multiprofessional practices considered innovative, such as the one that occurred in the fast-track of COVID-19. The present study suggests that the adequacy of the implemented biosafety protocols must be maintained so that the work environment is safer for both patients and health professionals in a post-covid era. In view of the implications that the pandemic has caused in the dental sector, it is likely that the oral health problems of the population have been considerably aggravated. Actions to mitigate the effects of the pandemic on oral health indicators must be quickly implemented by the public authorities